MYH11 rare variant augments aortic growth and induces cardiac hypertrophy and heart failure with pressure overload. - Zhen Zhou; Kgosi Hughes; Nisha Saif; Hyoseon Kim; Michael P Massett; Mingjie Zheng; Alana C Cecchi; Dongchuan Guo; David R Murdock; Ping Pan; Jelita S Clinton; Jun Wang; et al. (PLoS Genetics)
Smooth muscle cell-specific myosin heavy chain, encoded by MYH11, is selectively expressed in smooth muscle cells (SMCs). Pathogenic variants in MYH11 predispose to a number of disorders, including heritable thoracic aortic disease associated with patent ductus arteriosus, visceral myopathy, and megacystis-microcolon-intestinal hypoperistalsis syndrome. Rare variants of uncertain significance occur throughout the gene, including MYH11 p.Glu1892Asp, and we sought to determine if this variant causes thoracic aortic disease in mice. Genomic editing was used to generate Myh11E1892D/E1892D mice. Wild-type (WT) and mutant mice underwent cardiovascular phenotyping with and without transverse aortic constriction (TAC). Myh11E1892D/E1892D and WT mice displayed similar growth, blood pressure, root and ascending aortic diameters, and cardiac function up to 13 months of age, along with similar contraction and relaxation on myographic testing. The hypertension induced by TAC was similarly in Myh11E1892D/E1892D and WT mice, but mutant mice showed augmented ascending aortic enlargement and increased elastic fiber fragmentation on histology. Unexpectedly, male Myh11E1892D/E1892D mice undergoing TAC had decreased ejection fraction, stroke volume, fractional shortening, and cardiac output compared to similarly treated male WT mice. Importantly, left ventricular mass increased significantly due to primarily posterior wall thickening, and cardiac histology confirmed cardiomyocyte hypertrophy and increased collagen deposition in the myocardium and surrounding arteries. These results further highlight the phenotypic heterogeneity associated with MYH11 rare variants. Given that MYH11 is selectively expressed in SMCs, these results implicate a role of SMCs in the arteries of the heart contributing to cardiac hypertrophy and failure with pressure overload.